Turismo en Teotihuacán y San Martín de Las Pirámides: Su Influencia en el Capital Social de los Actores Locales / Tourism in Teotihuacan and San Martin De Las Pirámides: Its Influence on the Social Capital of Local Stakeholders - Ramírez Hernández, Omar Ismael; Cruz Jiménez, Graciela; Vargas Martínez, Elva Esther; Rodríguez Herrera, Ismael Manuel (Revista Rosa dos Ventos - Turismo e Hospitalidade, 2019)
RESUMEN Este artículo explora cómo el turismo influye en el capital social de los actores de los municipios de Teotihuacán y San Martín de las Pirámides, México, que territorialmente comparten la zona arqueológica de Teotihuacán, uno de los atractivos más importantes del País. Aunque en la literatura es relativamente reciente, el abordaje de este binomio ha generado interés entre la comunidad científica, porque son escasas las investigaciones sobre cómo el turismo puede influir en el capital social. La metodología que analiza el vínculo entre ambos elementos fue cualitativa e incluyó entrevistas con actores que residen en esos municipios, con el fin de conocer cómo el turismo ha modificado su capital social. Una de las contribuciones de este documento es integrar en el análisis a los actores sociales, públicos y privados, ya que su estudio se ha realizado de manera fragmentada. Complementariamente aporta evidencia empírica sobre cómo dicha actividad ha modificado el capital social de los actores que se le relacionan en dichos municipios. PALABRAS CLAVE Turismo. Capital Social. Actores Locales. Teotihuacán y San Martín de las Pirámides, México. ABSTRACT This article explores how tourism influences the social capital of the stakeholders in the municipalities of Teotihuacán and San Martín de las Pirámides, Mexico, which territorially share the archaeological zone of Teotihuacán, one of the country's most important attractions. The approach of this binomial is relatively recent, it has generated interest among the scientific community, since research on how tourism can influence social capital is limited. The methodology that analyzes the link between both elements was qualitative and included interviews with stakeholders residing in those municipalities, in order to know how tourism has modified its social capital. One of the contributions of this document is to integrate social, public and private stakeholders, in the analysis, since their study has been carried out in a fragmented manner. In addition, it provides empirical evidence on how this activity has modified the social capital of the stakeholders that relate to it in these municipalities. KEYWORDS Tourism. Social Capital. Local Stakeholders. Teotihuacán y San Martín de las Pirámides, México AUTORIA Omar Ismael Ramírez Hernández – Doctor. Profesor Universidad Autónoma del Estado de México, Centro Universitario Temascaltepec. Currículo: http://orcid.org/0000-0002-0874-5627. E-mail: omar.ramirez.hdez@hotmail.com Graciela Cruz Jiménez – Doctora. Profesora Universidad Autónoma del Estado de México, Facultad de Turismo y Gastronomía. Currículo: http://orcid.org/0000-0003-0608-4682. E-mail: gracicj@hotmail.com Elva Esther Vargas Martínez – Doctora. Profesora Universidad Autónoma del Estado de México, Facultad de Turismo y Gastronomía. Currículo: http://orcid.org/0000-0003-2657-2691. E-mail: elvacolegio@hotmail.com Ismael Manuel Rodríguez Herrera – Doctor. Profesor Universidad Autónoma de Aguascalientes. E-mail: imrodri@correo.uaa.mx REFERÊNCIAS Alder, P., & Kwon, S.-W. (2002). Social capital: prospects for a new concept. Academy of Management Review, 27(1), 17-40. Link Álvarez, A. (2005). La contribución del turismo al desarrollo integral de las comunidades receptoras. Aspectos teótico- metodológicos. Política y Sociedad, 42(1), 57-84. Link Andrade, M. (2008). Sociedad pesquera y desarrollo turístico pensado desde una cofradía de pescadores. Análisis cualitativo de la significación del Proyecto Mardelira. En Instituto de Estudios Sociales Avanzados (IESA) y Consejo Superior de Investigaciones Científicas (CSIC) (eds.), II Jornadas Turismo y Sociedad (57-84). Córdoba, España: IESA. CSIC. Link Arriagada, I., Miranda, F. & Pávez, T. (2004). Lineamientos de acción para el diseño de programas de superación de la pobreza desde el enfoque del capital social. Guía conceptual y metodológica. Santiago de Chile: CEPAL. Link Atria, R. (2003). La dinámica del desarrollo del capital social. Factores principales y su relación con movimientos sociales. En F. Miranda & I. Arriagada. Capital social: potencialidades analíticas y metodológicas para la superación de la pobreza (49-62). Santiago de Chile: Nacions Unidas-CEPAL. Link Baker, W. (1990). Market networks and corporate behavior. American journal of Sociology, 96, 589-625. Link Barbini, B. (2010). Dimensión sociocultural: actividad turística y capital social. En J. Mantero, B. Bernarda, G. Benseny, D. Castellucci, R. Dosso & C. Varisco. Turismo y territorio (185-226). Mar del Plata: Universidad Nacional de Mar del Plata. Link Barros, C. & Santos, C. (2009). Earnings of hotel managers: Comparing the human and social capital approach. Tourism Economics, 15(1), 87-103. Link Boonratana, R. (2010). Community-based tourism in Thailand: the need and justification for an operational definition. Kasetsart Journal Social Science, 31(2), 280-289. <a href="https://www.researchgate.net/publication/306502358_Boonratana_R_2010b_Community-based_Tourism_in_Thailand_The_Need_and_Justification_for_an_Operational_Definition_Kasetsart_Journal_Social_Science_Vol_312_280-289">Link Bourdieu, P. (1980). Le capital social. Actes de la Recherche en Sciences Sociales, 31, 2-3. Link Byrd, E., Bosley, H. & Dronberger, M. (2009). Comparisons of stakeholder perceptions of tourism impacts in rural eastern North Carolina. Tourism Management, 30(5), 693-703. Link Cacciutto, M. (2010). La aplicación de la teoría del capital social a los estudios turísticos. Faces, 16(34-35), 111-127. Link Coleman, J. (1990). Foundations of social theory. Cambridge: Harvard University Press. Conti, A. & Cravero, S. (2010). Patrimonio, comunidad local y turismo: La necesidad de la planificación para el desarrollo sostenible. Notas en Turismo y Economía, 1(1), 8-31. Link Corodeanu, D. & Nita, V. (2009). The network and the social capital - Important aces for tourism entrepreneurs. Revista de Turism, 7, 10-19. Link Dong, S., Burritt, R., & Quian, W. (2014). Salient stakeholders in corporate social responsibility reporting by Chinese mining and minerals companies. Journal of Cleaner Production, 84(1), 59-69. Link Dunham, L., Freeman, R., & Liedtka, J. (2006). Enhancing stakeholder practice: a particularized exploration of community. Business Ethics Quarterly, 16(1), 23-42. Link Durston, J. (2000). ¿Qué es el capital social comunitario? (Serie Políticas Sociales). Santiago de Chile: Naciones Unidas - CEPAL. Link Espinoza, V. (2008). Compromiso cívico y participación ciudadana en México. Una Perspectiva nacional y regional. América Latina Hoy, 48, 141-164. Link Fontana, A., & Frey, J. (2005). The Interview, from neutral stance to political involment. En N. Denzin, & S. Lincoln. The Sage Handbook of Qualitative Research (695-727). Londres: Sage. Fukuyama, F. (1995). Trust: The social virtues and the creation of prosperity. New York: Free Press. Gobierno del Estado de México. (2013). Pueblos con encanto del Bicentenario. Link Goeldner, C. & Ritchie, B. (2009). Tourism: principles, practices and philosophies. New Jersey: Jhon Wiley & Sons, Inc. González, M. & Iglesias, G. (2009). Impactos del turismo sobre los procesos de cohesión social Caibarién, Cuba. Estudios y Perspectivas en Turismo, 18(1), 53-68. Link Instituto Nacional de Antropología e Historia (2013, 15 de Diciembre). Instituto Nacional de e Historia. Link Instituto Nacional de Antropología e Historia (2018, 5 de Junio). Sistema Institucional Estadística de Visitantes. Link INAFED - Instituto Nacional para el Federalismo y el Desarrollo Municipal (2016). Link INEGI - Instituto Nacional de Estadística y Geografía (2015). Link Jamieson, N. (2014). Sport tourism events as community buildiers-how social capital helps the ‘locals’ cope. Journal of Convention & Event Tourism, 15(1), 57-68. Link Jovicic, D. (2014). Key issues in the implementation of sustainable tourism. Current Issues in Tourism, 17(4), 297-302. Link Kimbu, A. & Ngoasong, M. (2013). Centralised decentralisation of tourism development: a network perspective. Annals of Tourism Research, 40, 235-259. Link Krishna, A. & Uphoff, N. (2002). Mapping and measuring social capital: A conceptual and empirical study of collective action for concerving and developing watersheds in Rajasthan, India. En C. Grootaert & T. Van Bastelaer. The role of social capital in Development. An empirical Assesstment (85-124). Cambridge: Cambridge University Press. Ladkin, A. & Martinez, A. (2002). Collaborative tourism planning: a case study of Cusco, Peru. Current Issues in Tourism, 5(2), 71-93. Link Lorca, M. (2001). Turismo, capital social e industria cultural. En Colegio de Antropólogos de Chile (ed.), IV Congreso Chileno de Antropología (1192-1196). Santiago de Chile: Colegio de Antropólogos de Chile. Link Markwick, M. (2000). Golf tourism development, stakeholders, differing discourses and alternative agendas. Tourism Management, 21(5), 515-524. Link Martí, J. & Lozares, C. (2008). Redes organizativas locales y capital social: enfoques complementarios desde el análisis de las redes sociales. Portularia, 8(1), 23-39. Link Massey, D. (2009). Concepts of space and power in theory and in political practice. Documents d' Anàlisi Geogràfica, 55, 15-26. Link McGehee, N., Lee, S., O'Bannon, T. & Perdue, R. (2010). Tourism-related social capital and its a relationship with other forms of capital: An exploratory study. Journal of Travel Research, 49(4), 486-500. Link Merinero, R. (2008). Micro-clúster turísticos: El papel del capital social en el desarrollo económico local. Revista de Estudios Empresariales. Segunda Época, 2, 67-92. Link Monterrubio, J. (2013). Turismo no convencional. Impactos socioculturales. México: Trillas. Morales, G., & Hernández, J. (2011). Los stakeholders del turismo. Book of Proceedings. International Conference on Tourism & Management Studies (894-903). Algarve. Link Morgan, R. & Hunt, S. (1994). The commitment-trust theory of relationship marketing. Journal of Marketing, 58, 20-38. Link Muñoz, R., Rendon, M., Aguilar, A., García, M. & Altamirano, C. (2004). Redes de Innovación, un acercamiento a su identificación, análisis y gestión para el desarrollo rural. Michoacán, Mexico: Universidad Autónoma de Chapingo. Mura, P., & Tavakoli, R. (2014). Tourism and social capital in Malaysia. Current Issues in Tourism, 17(1), 28-45. Link Nahapiet, J. & Ghoshal, S. (1998). Social capital, intelectual capital, and the organizational advantage. Academy of Management Review, 23, 242-266. Link Noia, A., Avila, M. & Badaró, M. (2009). Desarrollo turístico y comunidad local valoraciones y expectativas de los residentes de Ilhéus-BA, Brasil. Estudios y Perspectivas en Turismo, 18(6), 634-654. Link Oliveira, M., Mendonça, K., & Fransualdo, F. (2014). Turismo e capital social: uma aproximação teórica. Pasos. Revista de Turismo y Patrimonio cultural, 12(2), 443-452. Link Park, D., Nunkoo, R., & Yoon, Y. (2015). Rural resident' attitudes to tourism and the moderating effects of social capital. Tourism Geographies: An international Journal of Tourism Space, Place and Environment, 17(1), 112-133. Link Park, D.-B., Lee, K.-W., Choi, H.-S., & Yoon, Y. (2012). Factors influencing social capital in rural tourism communities in South Korea. Tourism Management, 33, 1511-1520. Link Portes, A. (1998). Social Capital: its origins and applications in modern Sociology. Annual Review of Sociology, 24, 1-24. Link Portes, A., & Sensenbrenner, J. (1993). Embeddedness and immigration: Notes on the social determinants of económic action. American Journal of Sociology, 98, 1320-1350. Link Putnam, R. (1993). Making democracy work: civic traditions in moder Italy. Princeton: Princeton University Press. Ramírez, O., Cruz, G., & Serrano, R. (2019). Turismo y capital social: vacíos y oportunidades de investigación. Turismo y Sociedad, 24, 25-49. Link Ramírez, O., Cruz, G., & Vargas, E. (2018). Un acercamiento al capital social y al turismo desde el enfoque mixto y el mapeo de actores. Antropología Experimental, 18, 55-73. Link Richards, G. & Wilson, J. (2005). Social capital, cultural festivals and tourism in Catalunya. Anuario Turismo y Sociedad, 4, 170-181. Link Roloff, J. (2008). Learning from multi-stakeholder networks: issue-focussed stakeholder management. Journal of Business Ethics, 82(1), 233–250. Link Secretaría de Gobernación (2013). e-Local. Link Spanou, E. (2007). The impact of tourism on the sociocultural structure of cyprus. Tourismos: An International Multidiciplinary Journal of Tourism, 2(1), 145-162. Link Tavakoli, R., Mura, P. & Rajaratnam, S. (2017). Social capital in Malaysian homestays: exploring hosts' social relations. Current Issues in Tourism, 20(10), 1028-1043. Link Uphoff, N. (1999). Undestanding social capital: learning from the analisis and experience of participation. En P. Dasgupta & I. Serageldin. Social Capital: A multifaceted perspective (215-249). Washington D.C.: World Bank Publications. Link Uphoff, N. (2003). El capital social y su capacidad de reducción de la pobreza. En R. Atria, M. Siles, I. Agarriada, L. Robinson & S. Whiterford. Capital social y reducción de la pobreza en América Latina y el Caribe: en busca de un nuevo paradigma (115-145). Santiago de Chile: Naciones Unidas, CEPAL. Link Vijayanand, S. (2013). Stakeholders and public private partnerships role in tourism management. International Journal of Scientific & Engineering Research, 4(2), 1-11. Link Waligo, V., Clarke, J. & Hawkins, R. (2013). Implementing sustaiunable tourism: A multi-steakeholder involvement management framework. Tourism Management, 36, 342-353. Link Wilcox, B. (1981). The role of social support in adjusting to marital disruption: a network analysis. En B. Gottlieb. Social Networks and Social Support (97-115). California: Sage. Woolcock, M. (1998). Social capital and economic development: Toward a theorical synthesis and policy framework. Theory and Society, 27(2), 151-208. Link Woolcock, M., & Narayan, D. (2000). Capital social: Implicaciones para la teoria, la investigación y las políticas sobre desarrollo. Washington: Banco Mundial. Ying, T., & Zhou, Y. (2007). Community, goverments and external capitals in China's rural cultural tourism: A comparative study of two adjacent villages. Tourism Management, 28, 96-107. Link PROCESO EDITORIAL Recebido: 17 JAN 19; Avaliado: FEV-MAR; Aceito: 15 SET 19.